2022
DOI: 10.3389/fenrg.2022.945003
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Quasi/All-Solid-State Electrolytes for Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries have received increasing research interest due to their superior theoretical capacity, cost-effectiveness, and eco-friendliness. However, the commercial realization of lithium–sulfur batteries faces critical obstacles, such as the significant volume change of sulfur cathodes over the de/lithiation processes, uncontrollable shuttle effects of polysulfides, and the lithium dendrite issue. On this basis, the lithium–sulfur battery based on solid-state electrolytes was developed to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…[76][77][78][79][80][81] For low-molecular-weight polymers and polymers, the mode of ion conduction is similar to that of carbonate-based liquid electrolytes, which mainly occurs through diffusion in the form of solvation. 70,[82][83][84][85][86] It has been reported that the ionic conductivity in crystalline domain of polymer electrolytes is also higher than that in amorphous phase. In crystalline domains, polymer 281 Reprinted (adapted) with permission from Ref.…”
Section: Ion Transport Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…[76][77][78][79][80][81] For low-molecular-weight polymers and polymers, the mode of ion conduction is similar to that of carbonate-based liquid electrolytes, which mainly occurs through diffusion in the form of solvation. 70,[82][83][84][85][86] It has been reported that the ionic conductivity in crystalline domain of polymer electrolytes is also higher than that in amorphous phase. In crystalline domains, polymer 281 Reprinted (adapted) with permission from Ref.…”
Section: Ion Transport Pathwaymentioning
confidence: 99%
“…(4) Electronic conductivity of solid garnet electrolyte. 84,98,[120][121][122] Although the dendrite growth of lithium metal has been known since the 1960s, its potential mechanism still needs to be explored by researchers. In addition to lithium dendrites, the problem of high interface resistance is also an important factor affecting the electrochemical performance of batteries.…”
Section: Mechanism and Influencing Factors Of Lithium Dendritesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, all solid-state Li-S batteries have caught comparable attention by virtue of the following advantages: 1. the elimination of polysulfides shuttling; 2. the high mechanical modulus for inhibition of the lithium dendrites; 3. significantly improved incombustibility and safety. Generally, the SSEs in Li-S systems include gel/solid polymer electrolytes, inorganic-based solid electrolytes, and hybrid electrolytes, each of which possesses its strengths and weaknesses [203,204]. Note that even coordinating with SSEs, the conventional solid-liquid-solid conversion may also occur because of the formation and migration of highly soluble polysulfides in some special polymer or hybrid electrolytes [33].…”
Section: Asslsbs Based On Solid-phase Conversionmentioning
confidence: 99%